Biological and dosimetric evaluation of [11C]S-adenosyl methionine as a potential agent for prostate cancer diagnosis - Zoppolo Lencina, Florencia (2018)
Introduction: [11C]Choline ([11C]COL) has been widely used for prostate cancer diagnosis; however, this radiopharmaceutical is not recommended for patients with a low absolute PSA value (< 1 ng/mL) due to its limited sensitivity and specificity. The enzyme glycine N-methyltransferase is overexpressed during prostate cancer progression. It catalyses the methylation of glycine using S-adenosyl methionine (SAM or AdoMet) as a substrate. The authors have previously reported the automated radiosynthesis of [11C]SAM as a potential agent in the diagnosis of aggressive prostate cancer. In this study, a biological and dosimetric evaluation of [11C]SAM was performed. Results: The evaluation of [11C]SAM in a control group of healthy mouse model showed a relatively high tracer uptake in the kidneys and a rapid blood clearance. Most activity was eliminated in the urine. In a PC3 prostate cancer xenograft tumour model, [11C]SAM tumour uptake was significantly higher in relation to [11C]COL.The human dosimetry of [11C]SAM was estimated by extrapolating the preclinical results. The mean effective dose was 8.17 x 10-3 mSv/MBq and 2.49 x 10-3 mSv/MBq without and with bladder voiding, respectively. The results for kidneys in humans were comparable to those previously described for [11C]COL. Conclusions: The PET/CT studies showed a statistically higher in vivo tumour uptake of [11C]SAM compared to [11C]COL for the cancer xenograft model. The absorbed dose estimations of major organs and the effective dose were determined. The results suggested that [11C]SAM may be a potential PET tracer for prostate cancer diagnosis.